Surgery and anesthesia of ostrich - GIANNARAKOS (Δ.Γ. ΓΙΑΝΝΑΡΑΚΟΣ) D. G.; MOUSTARDAS (Ν. ΜΟΥΣΤΑΡΔΑΣ) N.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) J. (Journal of the Hellenic Veterinary Medical Society, 2018)
Breeding of ostriches has rapidly developed into an industry in Greece. With the increase in the number of these birds, there is a growing demand for veterinary services, related to their health care. The responsible veterinarian should be aware of the peculiarities of these animal species, in order to prevent and resolve the emerging problems. The present presentation discusses the most frequently occurring surgical problems in ostrich, such as injuries, fractures, dislocations, limb deformities, stomach impaction, intussusception, foreign bodies, prolapse of the cloaca, prolapse of the penis, administration of treatment and the induction of anesthesia.